Unlocking the post-transplant microenvironment for successful islet function and survival - Doherty, Daniel T.; Khambalia, Hussein A.; van Dellen, David; Jennings, Rachel E.; Piper Hanley, Karen (Frontiers in Endocrinology, 2023)
Islet transplantation (IT) offers the potential to restore euglycemia for patients with type 1 diabetes mellitus (T1DM). Despite improvements in islet isolation techniques and immunosuppressive regimes, outcomes remain suboptimal with UK five-year graft survivals (5YGS) of 55% and most patients still requiring exogenous insulin after multiple islet infusions. Native islets have a significant non-endocrine component with dense extra-cellular matrix (ECM), important for islet development, cell survival and function. Collagenase isolation necessarily disrupts this complex islet microenvironment, leaving islets devoid of a supporting framework and increasing vulnerability of transplanted islets. Following portal venous transplantation, a liver injury response is potentially induced, which typically results in inflammation and ECM deposition from liver specific myofibroblasts. The impact of this response may have important impact on islet survival and function. A fibroblast response and ECM deposition at the kidney capsule and eye chamber alongside other implantation sites have been shown to be beneficial for survival and function. Investigating the implantation site microenvironment and the interactions of transplanted islets with ECM proteins may reveal therapeutic interventions to improve IT and stem-cell derived beta-cell therapy.